Socio-emotional and personal development competencies as assets facilitating psychosocial adaptation in socially vulnerable secondary school students - Pardo, Victor Manuel; De La Ossa, Susana; Noreña, Manuel (Frontiers in Psychology, 2025)
Fostering positive developmental assets in the school student population could improve individuals' psychological adjustment processes and personal wellbeing. In view of the above, employing a non-probability selective, cross-sectional design, this study evaluates the association between socio-emotional and personal development competencies and psychosocial adaptation in a sample of 169 socially vulnerable secondary school students in the city of Cartagena de Indias (Colombia). Of these participants, 53.3% were female, and ages ranged from 11 to 19 years (M = 14.2; SD = 1.9). Participants completed scales that assessed their personal development (self-esteem, optimism, and satisfaction with life) and their socio-emotional development (empathy, attention, emotional clarity, and repair), as well as a psychosocial adaptation scale. Once data were processed through one-factor analysis of variance and multiple correspondence analysis (MCA), it was found that socio-emotional development assets associated with emotional intelligence had a significant relationship with the psychosocial adaptation processes of adolescents, despite the disadvantages, and inequalities of the social environment in which they grew. Further studies with adolescent populations in this social context are required to confirm these findings and, eventually, create psychoeducational programs that promote these positive developmental assets.